Cardiopulmonary Vascular Odyssey and Haemodynamic Conundrum: A Case Report of Total Anomalous Pulmonary Venous Connection - Anay Nanavaty; Dev Brahmbhatt; Vrusti Patel; Aatrayee Mudi; Deeksha Likhi (NMO Journal)
Total anomalous pulmonary venous connection (TAPVC) is a cyanotic congenital heart disease where all the pulmonary veins drain directly or indirectly into the right atrium. Each of these types can be further classified into two types based on the pulmonary veins – obstructive and non-obstructive. This case report describes a rare case of a 2-month-old male infant with an unobstructed supra-cardiac TAPVC. The patient presented with tachypnoea, cyanosis and feeding difficulties, which prompted a thorough examination. Unobstructed supra-cardiac TAPVC was revealed by the diagnostic evaluation using two-dimensional echocardiography. Supra-cardiac TAPVC repair surgery was performed, following which post-operative evaluations indicated that the patient had satisfactory biventricular functionality. This case emphasises the relevance of early detection of TAPVC, thereby highlighting the need for meticulous and prompt postnatal care. The primary insight lies in the crucial role of prenatal diagnosis in tertiary care facilities, which allows timely planning of delivery, postnatal surgical interventions and a better prognosis of the disease. By underlining the significance of early intervention in the management of such rare congenital cardiac diseases such as TAPVC, this case report offers valuable insights into the scientific community.